Kepatuhan Wajib Pajak Orang Pribadi: Pengaruh Cinta Uang Machiavellianism, Religiusitas, Whistleblowing System, Kepercayaan Terhadap Pemerintah - Amir Hidayatulloh; Indah Shofiyah; Agung Dwi Nugroho; Ervilia Agustine Wiharsianti; Faishal Prahatma Ganinda (ITB AAS INDONESIA, 2023)
This study aims (1) to analyze the factors that influence individual taxpayer compliance, and (2) to analyze whether religiosity moderates the effect of love of money on individual taxpayer compliance, and (3) to analyze whether religiosity moderates the effect of Machiavellianism on individual taxpayer compliance. The sample of this study is an individual taxpayer who is in Indonesia and has a Taxpayer Identification Number with a convenience sampling technique. Respondents of this study amounted to 294 respondents. The data analysis of this research used Partial Least Square (PLS) with the help of the WarpPLS tool. This study found that individual taxpayer compliance is influenced by love of money, machiavellianism, religiosity, and trust in the government. This study also found that religiosity moderated the effect of love and individual taxpayer compliance, but religiosity did not moderate the effect of Machiavellianism on individual taxpayer compliance.